Temperature Variation for Low Calcium Fly Ash Based Self Compacting Geopolymer Concrete - Kaitake , Mangal; Nawale , Suvarna; Akshay, Kand; Nikhil, Jagtap; B. G, Prof. Bhade (International Journal of Scientific Research in Civil Engineering, 2020)
Cement is commonly used as the main material to produce concrete; however, the process of production of cement is causing environmental problems. The amount of CO2 emission from cement industries due to the calcinations of limestone and combustion of fossil fuel is in the order of approximately one ton for every ton of cement produced. To produce environmentally friendly concrete called geopolymer, it was proposed that a new material could be produced by a polymerization reaction of alkali liquids with Si and Al as source materials of geological origin materials. Si and Al are derived from pozzolanic materials or aluminosilicate mineral powders, for example, powders of metakaolin or by-product of industrial and agricultural materials such as lignite ash and agricultural ashes. This research was conducted to study geopolymers made partly from < 45 μm powders of fly ash, bagasse ash. Sodium hydroxide concentration of 14 molar and sodium silicate (Na2SiO3) solutions were used as alkali activators by the mass ratio of Na2SiO3: NaOH at 2.5. The present work deals with the results of the experimental investigation carried out on fly ash based geopolymer concrete. The study analyses of fly ash in geopolymer concrete on compressive strength, split tensile strength. All tests were conducted according to Indian standard code procedure. The effect of percentage of fly ash in geopolymer concrete is studied in detailed. Test results for each variation are tabulated and discussed in details and some important conclusions are made.